2021
DOI: 10.1021/acs.jced.1c00632
|View full text |Cite
|
Sign up to set email alerts
|

Poly(propylene glycol) vs Sugar Alcohol-Based Aqueous Biphasic System to Extract Drugs and Subsequent Recovery of the Polymer

Abstract: A carbohydrate-based aqueous biphasic system (ABS) has been designed by adding an aqueous solution of sugar alcohols (D-mannitol and glycerol) to poly(propylene glycol) (PPG#400). The phase diagrams of the ABSs have been constructed using the turbidometric titration method at 309 K. The tie-line lengths and the slope of tie lines of the system have been obtained using the gravimetric method. The use of sugar alcohol to replace the salt-rich phase for phase separation makes the ABS apt for extracting different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although the isolation step is outside of the scope of the experimental study reported here, some suggestions are provided with respect to how to isolate and reuse the ABS components (dashed lines in Figure 10 ) to further emphasize the sustainable character of the process. RSV could be easily recovered from the PPG-rich phase by antisolvent crystallization, whereby adding water as antisolvent can significantly lower the solubility of hydrophobic polyphenol [ 61 ]. Isolation from the IL matrix could be achieved using affinity resins.…”
Section: Resultsmentioning
confidence: 99%
“…Although the isolation step is outside of the scope of the experimental study reported here, some suggestions are provided with respect to how to isolate and reuse the ABS components (dashed lines in Figure 10 ) to further emphasize the sustainable character of the process. RSV could be easily recovered from the PPG-rich phase by antisolvent crystallization, whereby adding water as antisolvent can significantly lower the solubility of hydrophobic polyphenol [ 61 ]. Isolation from the IL matrix could be achieved using affinity resins.…”
Section: Resultsmentioning
confidence: 99%
“…Thermoseparation, deprotinization, ultrafiltration, adsorption, etc. are some of the recognized techniques to recover the polymer-rich phase of the ABS. ,, In the present work, block copolymers, which are highly thermosensitive in nature, have been used to form the polymer-rich phase of the ABS. Thus, after the extraction experiment, first, the thermoseparation technique has been used to recover the polymer.…”
Section: Introductionmentioning
confidence: 99%